Optoelectronic performance of Jatropha oil-derived poly(ethyl carbamate) gel polymer electrolyte as quasi-solid-state solution for photoelectrochemical cells - Chai, K.L; I.M., Noor; Lee, Tian Khoon; Su’ait, M.S.; Ahmad, A. (Springer Science and Business Media Deutschland GmbH, 2024)
A biopolymer derived from Jatropha oil-based poly(ethyl carbamate) (PUA) has been used as gel polymer electrolyte (GPE) in optoelectronic devices and photoelectrochemical cells (PEC) as photodiode devices. The quasi-solid-state photodiode device was characterized through photo current–voltage analysis, photogenerated charge carrier dynamic analysis, electrochemical impedance spectroscopy (EIS) analysis, and voltammetry analysis. Sample A2 biopolymer electrolyte (95 wt.% PUA, 5 wt.% LiI, 5 wt.% I2) revealed the highest ionic conductivity (2.34 ± 0.01) × 10−4 S cm−1 and power conversion efficiency (5.09 ± 0.23) %, along with the highest short-circuit current density (17.80 ± 0.41) mA cm−2, open-circuit voltage (0.52 ± 0.01) V, and fill factor (0.55 ± 0.04). respectively. Moreover, sample A2 biopolymer electrolyte featuring a triiodide ion diffusivity of 1.82 × 10−8 cm2 s−1 demonstrated electrochemical stability up to 2.1 V and remained functional for a duration of 2000 cycles. The charge dynamic mechanism in the PEC proved that sample A2 biopolymer electrolyte recorded lowest values of Rs, Rpt, Rct, and Rd of (18.60 ± 0.01) Ω, (1.20 ± 0.01) Ω, (10.0 ± 0.01) Ω, and (11.50 ± 0.01) Ω, respectively